Mathematical Analysis for Engineers - Dacorogna, Bernard, 1953-, author 259869; Tanteri, Chiara, author 551127 (London : Imperial College Press ; Hackensack, NJ : Distributed by World Scientific Pub., 2012)
This book follows an advanced course in analysis (vector analysis, complex analysis and Fourier analysis) for engineering students, but can also be useful, as a complement to a more theoretical course, to mathematics and physics students.The first three parts of the book represent the theoretical aspect and are independent of each other. The fourth part gives detailed solutions to all exercises that are proposed in the first three parts.